2015
DOI: 10.4236/jmmce.2015.33019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Thickness and Core Density on Low Velocity Impact Behavior of Sandwich Panels with PU Foam Core

Abstract: Composite sandwich structures are highly proven materials that provide high strength to weight ratio. However research works are still being carried out in the area of impact characteristics of sandwich composites. This paper provides a better understanding on the effect of core density and core thickness of sandwich panels subject to low velocity drop test. Specific energy absorption capacity of sandwich panels is obtained and factors affecting the same are explored with facings made of woven glass fiber lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Although the H25 specimen was heavier, it absorbed higher specific energy than the H15 specimen. Similar results were observed in another study [49]. Authors found that the increase in the foam core thickness could improve the specific energy absorption amount of the same skinned sandwich composite under an impact event.…”
Section: Single Foam Core Sandwich (Sfs) Design With Ashwood Skinsupporting
confidence: 87%
“…Although the H25 specimen was heavier, it absorbed higher specific energy than the H15 specimen. Similar results were observed in another study [49]. Authors found that the increase in the foam core thickness could improve the specific energy absorption amount of the same skinned sandwich composite under an impact event.…”
Section: Single Foam Core Sandwich (Sfs) Design With Ashwood Skinsupporting
confidence: 87%
“…Polyurethane (PU) foam has a porous structure, low production cost, easy processing, and good controllability, all of which make it a superior candidate for cushioning materials. Such composites can absorb energy caused by an impact or vibration by breakage, fracture, bending, and friction against porous cell walls, thereby protecting commodities [1]. The addition of nanoparticles, graphene, carbon nanotube, and silica can improve the mechanical properties of PU foam [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of research studies available that have focused on the dynamic impact behavior of foam core sandwich composites [1021]. Most of these prior studies have focused on low-velocity impact loading at room temperature (25°C).…”
Section: Introductionmentioning
confidence: 99%
“…Loganathan et al. [16] explored the effect of core thickness (10 and 14 mm) and density (70, 100 and 200 kg/m 3 ) of bi-directional woven E-glass/epoxy sandwich composite with polyurethane foam core under three different impact velocities (1.401, 2.426 and 3.123 m/s). They observed that the samples absorbed more energy with increasing core density and thickness.…”
Section: Introductionmentioning
confidence: 99%